Development, Validity, and Reliability of Resilient Therapy Counseling Intervention Focusing on Self-Concept for Adolescents (RT-SC-A) - Amalia, Madihie; Sidek, Mohd Noah; Maznah, Baba; Wan Marzuki, Wan Jaafar (Faculty of Cognitive Science and Human Development, 2014)
The aim of this paper is to introduce Resilient Therapy Intervention focusing on self-concept for adolescents (RT-SC-A) and its development processes. This includes the validity and reliability tests for RT-SC-A. The interventions are a collection of resilience activities to increase orphaned-adolescents’ resiliency (Roose et al., 2010; Mohd Majid Konting, 2004). A descriptive research design was employed in this research. Findings showed the high value of content validilty based on the five criteria suggested by Russell (1974) and Sidek Mohd Noah (2001). Four counseling experts were chosen to test and evaluate the intervention. Feedbacks were received from experts as guidance to improve the Resilient Therapy Intervention in order to ensure the quality of intervention contents. A validation stage was carried out by four expert counselors, and Cronbach alpha .83 was obtained. A group of orphans from aged 13 to 17 years was piloted to check the module’s reliability. As a result, Cronbach alpha .93 was obtained. High score from the content validity was achieved and proven that the Resilient Therapy Intervention could assist counselors or group facilitators in re-changing orphaned-adolescents’ self-concept, later to improve their resiliency as stated in the objective. Implications from theoretical and practical are also discussed.